AB0680 BASELINE CHARACTERISTICS OF PATIENTS ENROLLED IN THE ONGOING SIRENA STUDY, A NATIONAL PROSPECTIVE OBSERVATIONAL REGISTRY IN SPONDYLOARTHRITIS SUBJECTS. (2nd June 2020) - Zabotti, A.; Gabrielli, A.; Selmi, C.; Grembiale, R. D.; Ramonda, R.; Dagna, L.; D'angelo, S.; Gerli, R.; De Vita, S.; Marelli, S.; Frigerio, D.; Favalli, E.
Abstract : Background: There is a paucity of epidemiological data in Early Arthritis. SIRENA is an Italian prospective observational study in SpA patients, naïve to conventional, targeted and biological DMARDs. Objectives: To present the baseline data, including demographic characteristics and patterns of clinical presentation, for the population enrolled between June 2017-February 2019. Methods: At the study entry, patients are diagnosed, newly or confirmed, according to ASAS criteria and classified in subjects with predominant axial (AX) or with mainly peripheral (PER) manifestations. Diagnostic delay, subtypes of SpA are evaluated as well as clinical features (i.e. presence of dactylitis, enthesitis, involvement of skin/nails/other organs). Results: In 23 italian sites, 282 patients were enrolled. Baseline data are shown in Table 1. 18% of the patients were obese (maximum BMI=39.7), 22% overweight. Diagnostic delay was registered for 58.1% patients with a mean delay of 57.1 months. Main reasons of the delay were incorrect referrals (44%) and previous misdiagnosis (27%). The most frequent type of SpA was psoriatic arthritis (54.3%), followed by ankylosing spondylitis (18.5%), undifferentiated SpA (11.5%), non-radiographic axial SpA (8.2%), and enteropathic SpA (7.5%). The majority of patients reported as first symptom peripheral arthritis and inflammatory back pain, followed by enthesitis. The most frequently reported comorbidities were psoriasis (50.4%) and cardiometabolic and gastrointestinal diseases (30.1% and 15.7%, respectively) - Table 2. To the 154 psoriatic arthritis (PsA) patients, CASPAR classification criteria were also applied, with a performance of 95% and a mean score of 3.64. Conclusion: SIRENA is the first Italian Disease Registry for SpA patients. The above results are in line with the few evidences found in literature (1), confirming the representativeness of our sample. In case of PsA, our results confirm that the accordance between ASAS and CASPAR criteria is very high. References: [1]Tayel et al. Rheumatol Int 2012; 32:2837-42. Acknowledgments: This study was sponsored by Janssen Italy. We thank the Investigators and their staff at all of the study sites. Disclosure of Interests: Alen Zabotti Speakers bureau: Celgene, Novartis, Janssen, Armando Gabrielli Grant/research support from: Pfizer, Speakers bureau: Pfizer, Actelion, Carlo Selmi Grant/research support from: AbbVie, Janssen, MSD, Novartis, Pfizer, Celgene, and Leo Pharma, Consultant of: Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, Roche, and Sanofi-Regeneron, Speakers bureau: AbbVie, Aesku, Alfa-Wassermann, Bristol-Myers Squibb, Biogen, Celgene, Eli-Lilly, Grifols, Janssen, MSD, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB Pharma, Rosa Daniela Grembiale: None declared, Roberta Ramonda Speakers bureau: Novartis, Celgene, Janssen, Pfizer, Abbvie, Lilly, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI, Salvatore D'Angelo Speakers bureau: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sanofi, and UCB, Roberto Gerli: None declared, Salvatore De Vita Consultant of: Roche, Human Genome Science, Glaxo Smith Kline and Novartis, Silvia Marelli Employee of: Janssen, Daniela Frigerio Employee of: Janssen, Ennio Favalli Speakers bureau: BMS, Eli-Lilly, MSD, UCB, Pfizer, Sanofi-Genzyme, Novartis and Abbvie